Pola Spasial-Temporal Epidemi Demam Chikungunya dan Demam Berdarah Dengue di Kota Yogyakarta Tahun 2008 - Citra Indriani, Anis Fuad, Hari Kusnanto (Fakultas Kedokteran Universitas Gadjah Mada, 2011)
Spatial-Temporal Pattern Comparison Between ChikungunyaOutbreak And Dengue Hemmorhagic Fever IncidenceAt Kota Yogyakarta 2008Background: Explosive re-emergence of chikungunya fever has been started since 2004 and affected millions people in worldwide i.e. Indian Ocean, India, Europe, Asia including Indonesia. On January 2008, 59 new cases of chikungunya fever was reported by the Kota Yogyakarta health office meanwhile the province laboratory had no capability to perform laboratory examination to confirm the diagnosis. Control measures were already taken, but it seemed not effective, cases were spread and increased progressively by weeks and non-vector born disease which has similar sign and symptoms was thought to be the cause. Based on the same vector withdengue hemorrhagic fever transmission, an ecological approach using GIS was taken to compare the spatial-temporal pattern between chikungunya and DHF.Objective: The objective of this study was to compare the spatial-temporal pattern between chikungunya fever outbreak and dengue hemorrhagic fever incidence.Method: This study was use ecological study approach which uses integrated GIS, remote sensing and statistic technique. We collected total of 802 chikungunya and 498 dengue cases in ten months (November 2007 – August 2008) and secondary data on environmental variable includes population density, vegetation density, building density, land use, larvae index and climate. Location of cases was obtained using GPS. Epidemic curve were plotted to identify the disease trend. Space time permutation was used to identify disease clustering.Result: Temporal trend analysis show similarity pattern between chikungunya and DHF, increasing trend was found few weeks following heavy rain. There were positive correlations between diseases and population density, building density. Chikungunya and DHF cases were tended to occur in residential land use which close to the commercial land use. Spatial-temporal clustering was observed on both diseases demonstrating variation in local infection pattern. There was similarity on disease cluster occurrence between chikungunya and DHFConclusion: We show spatial-temporal pattern similarity between chikungunya outbreak and dengue hemorrhagic incidence, nevertheless laboratory confirmation is important and should be provided. This study provides useful information for urban public health management. Further study is needed to develop model in vector born early warning system using GIS and remote sensing.Keywords: dengue, chikungunya, GIS, spatial-temporal pattern, environmental epidemiology